2021
DOI: 10.3389/fcell.2021.642650
|View full text |Cite
|
Sign up to set email alerts
|

A Novel CpG Methylation Risk Indicator for Predicting Prognosis in Bladder Cancer

Abstract: PurposeBladder cancer (BLCA) is one of the most common cancers worldwide. In a large proportion of BLCA patients, disease recurs and/or progress after resection, which remains a major clinical issue in BLCA management. Therefore, it is vital to identify prognostic biomarkers for treatment stratification. We investigated the efficiency of CpG methylation for the potential to be a prognostic biomarker for patients with BLCA.Patients and MethodsOverall, 357 BLCA patients from The Cancer Genome Atlas (TCGA) were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…These results may partially explain the aggressive clinical behavior and a more advanced presentation of UTUC. Several previous publications have established a prognostic influence of methylation in UC [ 27 , 28 ], and we found that the methylation levels of some CpG sites were consistent in high-risk patients and in the Methy-High subgroup of UC patients (Additional file 1 : Fig. S7E).…”
Section: Discussionsupporting
confidence: 67%
“…These results may partially explain the aggressive clinical behavior and a more advanced presentation of UTUC. Several previous publications have established a prognostic influence of methylation in UC [ 27 , 28 ], and we found that the methylation levels of some CpG sites were consistent in high-risk patients and in the Methy-High subgroup of UC patients (Additional file 1 : Fig. S7E).…”
Section: Discussionsupporting
confidence: 67%
“…Among the 39 studies that adopted clustering-based workflows (5, 18-23, 29, 32-35, 37-39, 43, 45-47, 50, 53-57, 61, 62, 64, 69, 70, 75, 77-80, 83, 84, 87, 88), most started with a preliminary screening of CpG sites (Figure 4.1). The most frequently used pre-selection approach was selecting CpG sites that were significantly associated with prognosis by first performing univariable Cox regression analysis, and then performing multivariable Cox analysis with adjustment for clinical variables.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Feng et al ( 2021 ) used limma to identify significant DMCs between chemoresistant and chemosensitive ovarian cancer patients. To identify methylation patterns that are correlated with DEGs, Guo et al ( 2021 ) screened differentially expressed CpG sites between bladder tumor and adjacent normal tissues using limma. Li et al ( 2021 ) identified DMCs by comparing all tumor and normal samples through unpaired t -tests, and paired tumor and normal samples through paired t -tests.…”
Section: Methylation Feature Selectionmentioning
confidence: 99%
“…Li et al ( 2021 ) used the strategy of stepwise selection to identify prognosis-associated CpGs. Guo et al ( 2021 ) employed a backward elimination procedure, support vector machine recursive feature elimination (SVM-RFE), to select candidate CpGs. They ranked variables based on nonlinear SVM and SVM for survival analysis and improved the performance of the classical RFE algorithm (Guyon et al, 2002 ).…”
Section: Methylation Feature Selectionmentioning
confidence: 99%